Effect of Drought Stress on Growth and Productivity of Local Rice Ciherang, and Aromatic Rice Sintanur - Mohammad Ali Mudhor; Erlin Susilowati; Eka Nurmala Sari (Agrotechnology Research Journal, 2025)
This study examined the morphological and physiological responses of two rice varieties to drought stress to identify adaptive characteristics that support plant resistance. Parameters analyzed included leaf rolling rate, stomatal density, chlorophyll content, proline accumulation, and the number of full and hollow grains per panicle. Results showed that increased drought stress triggered more intense leaf rolling, decreased stomatal density, and reduced chlorophyll content, which negatively affected photosynthesis and yield. Proline accumulation increased significantly, suggesting its important role in osmoregulation and stress tolerance. Variety CIherang (V1) showed better adaptability than Variety Sintanur (V2), characterized by efficient stomatal adjustment and higher proline accumulation. The decreased number of full grains and increased hollow grains at high stress levels confirmed the impact of drought on productivity. These findings indicate that leaf rolling and proline accumulation can be used as indicators for the selection of drought-resistant varieties, supporting the development of adaptive rice in drought-prone areas due to climate change